(2x-1)(x-2)(2x²+7x+2)=-20x²(x-4)(x+5)(x+10)(x-2)=18x²

(2x-1)(x-2)(2x²+7x+2)=-20x² (x-4)(x+5)(x+10)(x-2)=18x²
Гость
Ответ(ы) на вопрос:
Гость
(2x-1)(x-2)(2x²+7x+2)=-20x² (2x²-5x-2)(2x²+7x+2)=-20x² 4x (В 4) +14х (в кубе)+4 x² - 10 х(в кубе)-35 x² -10 х -4 x² -14х-4=-20x² 4x (В 4) + 4х (в кубе) -35 x²- 24х - 4+ 20 x²=0 4x (В 4) + 4х (в кубе) - 15 x²- 24х - 4=0 4x (В 4) + 4х (в кубе) - 24х - 4=15 x² 4(4х (в кубе)+ 4x²- 6х-1) =15 x² 4 =15 x²   или (4х (в кубе)+ 4x²- 6х-1) =15 x² 4:15 = x²  или 4х (в кубе) -11x² - 6х=1 х= корень 4:15 или х(4x² -11x - 6) = 1                                  х=1 или 4x² -11x - 6= 1                                               4x² -11x - 7=0                                                 Д= 121 -4* 4*(-6) =121 +96= 217                                                   Д= корень 217                                               
Не нашли ответ?
Ответить на вопрос
Похожие вопросы